Cal Poly's First Baccalaureate Commencement (1942)
Cal Poly's first baccalaureate graduates receive B.S. diplomas at Cal Poly's first college commencement on May 29, 1942 in the air-conditioning building auditorium. Twenty-six students graduated with a bachelor of science and twenty-six students received technical or vocational diplomas. State Superintendent Walter F. Dexter hands out diplomas while President Julian McPhee (hand in pocket) announces names.